An epidemiological study to find out the seroprevalence of Hepatitis B in a rural population of Kashmir valley - Fazili, Anjum Bashir; Shah, Rohul Jabeen; Shah, Zaffar Amin; Iqbal, Qazi Mohammad; Mushtaq, Beenish; Ahmad, Feroz; Parray, Javed Ahmad (International Journal Of Community Medicine And Public Health, 2017)
Background: Hepatitis B continues to pose a tremendous burden of disease with approximately 240 million people having chronic hepatitis B virus (HBV) infection globally. The prevalence of HBV infection varies widely, with rates ranging from 0.1% to 20% in different parts of the world. Methods: This Community based Cross sectional study was carried out for a period of one year (2015-2016) in bock Hajin of Kashmir to find out the seroprevalence of Hepatitis B and various risk factors associated with it.1861 subjects consented and participated in the study. A semi structured, pre tested, self-designed questionnaire was used to gather requisite information. Both screening as well as confirmatory tests were used to find out the seroprevalence of HBsAg in the study population. Results: Out of 1861 participants, 65.1% were females and 34.9% were males. All study participants were Muslims with 64.4% belonging to Sunni sec. 67.3% belonged to age group 10-40 years. Prevalence of hepatitis B infection in the study population was 0.9%. Gender, occupation, education and treatment by quacks were significantly associated with seropositivity. Only 76 (4.1%) of the participants had some knowledge about hepatitis B. Conclusions: The study reveals that the seroprevalence of hepatitis B is very low in the study population. It also reflects a low awareness level of population regarding hepatitis B infection thus demanding timely intervention in the form of awareness campaigns to keep transmission under check.